Tobacco use and alcohol consumption associated with sociodemographic factors among college students (Acta Scientiarum. Health Sciences, 2015)
The aim of this study was to determine the association between sociodemographic variables and behaviors and the use of tobacco and alcohol among students of the Federal University of Paraná. Risk behavior of 1.599 students was obtained from the Youth Risk Behavior Surveillance. The association analysis estimated which college students are more vulnerable to the use of tobacco and alcohol. The subjects who smoked more often were older, unmarried, senior students, residing without family and with low socioeconomic status (p < 0.05).Considering alcohol consumption, the subjects were older, male, single, night period students (p < 0.05). Excessive alcohol consumption was also more likely among older human sciences students, of the night shift and with low socioeconomic status (p < 0.05).